Strategy for Increasing Working Performance of Broiler in The Integrated Poultry Industries: Study Case in Sierad Produce Co - Abieta Fellyanti Bhuwana Putri; Marimin Marimin; Imam Teguh Saptono (School of Business, IPB University (SB-IPB), 2018)
The aims of the research are to: identify the supply chain of broiler in Sierad Produce Co; calculate the value added of activities occurring in some supply chain stakeholders; measure the supply chain working performance of broiler in Sierad Produce Co; and formulate strategies recommended to increase the supply chain working performance of broiler in Sierad Produce Co. This research used data analysis methods: Asian Productivity Organization (APO) for analyzing the general situation of supply chain; Hayami mathematical model for processing the data regarding the value added analysis of supply chain stakeholders; SCOR Model for metrical plan of supply chain working performance measure; Analytic Hierarchy Process (AHP) method for determining the metrical weights of supply chain working performance measure; and Analytic Network Process (ANP) for determining the priority of strategic alternatives to increase the supply chain working performance of broiler in Sierad Produce Co. The results of value added analysis have shown that the food processing industries (downstream sector) enjoy the highest value added. Accordingly, the researcher summarized a number of points as follows: Firstly, the highest capital return in the poultry industry is caused by technological factors. Secondly, the supply chain working performance measure result shows that low working performance of commercial farm is caused by non-adaptable company in fulfilling the demand of Chicken Slaughter House. The last, the working performance increase strategic formulation result has shown that increase of Human Resources’ skill or ability is the most influential strategical alternative to supply chain working performance increase in Sierad Produce Co.Keywords: AHP, ANP, poultry industries, supply chain management, SCOR